The European language portfolio (ELP) in Slovenian primary education - Sešek, Urška (Linguistica (Ljubljana), 2014)
The European Language Portfolio (ELP) is a unique, pan-European language learning material, aimed at supporting life-long language learning and the development of learner autonomy and intercultural competences. The article outlines the ELP's origins, structure and functions, and its impact on foreign language learning and teaching in Europe. Of the Slovenian ELP models, the two intended for primary school have been the most widely-implemented. Their implementation was the subject of a three-year study, in the context of a national piloting project involving over 600 learners and 100 teachers, held in 2008 and 2009. Due to the complexity and scope of the study, this article focuses on the perspective of the teachers, as carriers of pedagogical innovation. The results show that the two versions of ELP validated for Slovenian primary schools are judged by the teachers as being quality materials which are well-adapted to the learners. This pilot period yielded a number of positive effects in both teaching and learning, most notably more communicative and learner-centered instruction formats, and an increase in the learners' motivation and self-assessment skills. The main concern was strained lesson planning, due to the fact that the ELP was not integrated into the curriculum. Overall, the study shows that, of the two parallel functions of the ELP, the documenting of language learning and achievement is more readily embraced, while the self-assessment and self-directedness aspects involve a paradigm shift, which would require further sustained and widely-supported implementation. This would enable the full unfolding of the ELP's great potential for the promotion of language and intercultural competences and lifelong learning in Slovenia and in Europe.
Keywords: attitude des enseignants; EJL; Evropski jezikovni listovnik; osnovne šole; PEL; Portfolio européen des langues; Slovenia; Slovenija; tuji jeziki; učitelji